2006
DOI: 10.1038/sj.cdd.4401859
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of CD40-induced apoptosis of carcinoma cells involving TRAF3 and JNK/AP-1 activation

Abstract: Membrane-presented CD40 agonists can induce apoptosis in carcinoma, but not normal homologous epithelial cells, whereas soluble agonists are growth inhibitory but not proapoptotic unless protein synthesis is blocked. Here we demonstrate that membrane-presented CD40 ligand (CD154) (mCD40L), but not soluble agonists, triggers cell death in malignant human urothelial cells via a direct mechanism involving rapid upregulation of TNFR-associated factor (TRAF)3 protein, without concomitant upregulation of TRAF3 mRNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
106
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(129 citation statements)
references
References 46 publications
19
106
0
3
Order By: Relevance
“…In agreement with our results, it has been reported that membranebound CD40L but not rsCD40L upregulated TRAF3 in urothelial cancer cells but not normal urothelium (9). However, we are the first to show that there is a reciprocal downregulation of TRAF6 in response to membrane bound CD40L.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our results, it has been reported that membranebound CD40L but not rsCD40L upregulated TRAF3 in urothelial cancer cells but not normal urothelium (9). However, we are the first to show that there is a reciprocal downregulation of TRAF6 in response to membrane bound CD40L.…”
Section: Discussionsupporting
confidence: 93%
“…Low levels of CD40 ligation promote cell survival/proliferation, whereas high levels induce growth arrest/ apoptosis (5-7). The precise form of the CD40 stimulus also affects these responses, with the most profound effects in carcinoma cells being induced by membrane-bound rather than recombinant soluble CD40L (rsCD40L) (8,9). The signaling pathways underlying these differential responses are yet to be fully characterized, and there is controversy in the field as to the relative contribution of CD40-induced activation of the JNK/AP-1 MAPK pathway versus upregulation of membrane-bound ligands of the TNF family in CD40L-mediated carcinoma cell apoptosis (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether RAd-hCD40L infection results in CD40 stimulation, lysates from EJ cells infected with CD40L or b-galactosidase-expressing virus were analyzed for c-Jun N-terminal kinase (JNK) activation, a pathway known to be activated by soluble CD40L or agonistic CD40 mAb treatment of malignant cells. 10,30 As shown in Figure 1d, RAd-hCD40L induced sustained phosphorylation of JNK compared with rsCD40L protein that only transiently activated this pathway.…”
Section: Adenovirus-mediated Expression Of Human Cd40l In Vitromentioning
confidence: 86%
“…Concomitant with this idea, RAd-hCD40L but not soluble CD40L displays prolonged engagement of the JNK signaling pathway (Figure 1d), which has been implicated in the pro-apoptotic effects of CD40 ligation. 30 The death-inducing and inflammatory activity of membrane-tethered FasL, a well-studied TNF family member, is regulated by soluble FasL, which is shed from the membrane-bound form of the molecule by putative metalloproteinase(s). 32,33 RAd-FasL-infected cells secrete soluble FasL that reduces the cytotoxic effects and therapeutic capacity of this virus.…”
Section: Discussionmentioning
confidence: 99%